Spatiotemporal Dynamics of Land Use Carbon Balance and Its Response to Urbanization: A Case of the Yangtze River Economic Belt - Xinling Jiang; Xu Chu; Xinyu Yang; Ping Jiang; Jing’an Zhu; Zhongyao Cai; Siqi Yu (Land)
Urbanization and its impact on land use and land cover change are key drivers of global carbon balance shifts. Understanding the spatiotemporal evolution of carbon balance in relation to urbanization helps optimize regional planning and sustainable development. This study develops a city-level land use carbon balance system to quantify the spatiotemporal dynamics of land use carbon balance across 130 cities in the Yangtze River Economic Belt (YREB). Moran’s Index is applied to assess the spatial correlation of carbon balance, and the Environmental Kuznets Curve (EKC) is used to explore the relationship between urbanization levels and net carbon emissions. The results show the following: (1) From 2005 to 2021, land use carbon absorption in YREB cities remained relatively stable, whereas carbon emissions increased. Net carbon emissions increased by 574.61, 456.16, and 1163.60 Mt C in the upper, middle, and lower reaches, respectively. Nearly 98% of the cities exhibited a carbon balance index greater than 1, indicating a carbon deficit. Carbon emission intensity displayed a decreasing trend, with the most significant reductions observed in the middle reaches. (2) Land use carbon balance exhibits significant positive spatial correlation, with cities in the northeastern lower reaches and southwestern upper reaches forming “high–high” and “low–low” net carbon emission clusters. (3) Urbanization and per capita net carbon emissions followed an inverted “N”-shaped curve, with turning points at around 30% and 85% urbanization. This study provides insights into optimizing land use carbon management amidst urban growth in the YREB.